Effectiveness of Brain-based Teaching Strategy on Students’ Achievement and Score Levels in Heat Energy - Abiodun Adekunle Bada (Journal of Innovation in Educational and Cultural Research, 2022)
Physics is an important subject taught at the secondary level in Nigeria but the achievement of students in the subject is a concern to science educators. This study investigated the effectiveness of brain-based teaching strategy (BTS) on students’ achievement and score levels on the concept of heat energy. This investigation adopted the pretest, posttest, randomized control group quasi-experimental design. Simple random sampling technique was used to select two schools used for this study. Two research questions were raised to guide the study. Likewise, two null hypotheses were tested for acceptance or otherwise at 0.05 significance level. The sample involved ninety nine senior school students randomly selected from two schools in Ondo, Nigeria. Two instruments were used to gather data with internal consistency of 0.74 using Kuder Richarson Formular 21. The data collected were analysed using mean, t-test and Analysis of Covariance (ANCOVA). Findings from this investigation reveals that brain-based teaching strategy has significant effect on physics students’ achievement and score levels in the concept of heat energy. This study concludes that brain-based teaching strategy should be used to teach heat energy at secondary school level in order to better students’ grades.